2007
DOI: 10.1080/13576500601112358
|View full text |Cite
|
Sign up to set email alerts
|

Direction of hair whorl and handedness

Abstract: We recorded the direction of hair whorl rotation in samples of male right- and non-right-handers. The data corroborate those of Klar (2003) in showing equal numbers of clockwise and anti-clockwise whorls in non-right-handers but an excess of clockwise whorls in right-handers. The findings support the view that in some proportion of the population direction of coiling arises as a consequence of random events occurring during early (pre-natal) development of the nervous system, while in the remainder of the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
4
8
1
Order By: Relevance
“…We found no significant relationship between hair whorl rotation pattern and handedness, contrasting with two studies (Beaton & Mellor, 2007;Klar, 2003), but consistent with the others (Annett, 1985;Collins, 1977;Jansen et al, 2007;Newman, 1934;Rahman et al, 2009). Also, we found no significant relationship between hair whorl rotation pattern and sexual orientation, contrasting with previous results in a much smaller sample (Klar, 2004), but consistent with another smaller sample (Rahman et al, 2009).…”
Section: Hair Whorlcontrasting
confidence: 70%
See 1 more Smart Citation
“…We found no significant relationship between hair whorl rotation pattern and handedness, contrasting with two studies (Beaton & Mellor, 2007;Klar, 2003), but consistent with the others (Annett, 1985;Collins, 1977;Jansen et al, 2007;Newman, 1934;Rahman et al, 2009). Also, we found no significant relationship between hair whorl rotation pattern and sexual orientation, contrasting with previous results in a much smaller sample (Klar, 2004), but consistent with another smaller sample (Rahman et al, 2009).…”
Section: Hair Whorlcontrasting
confidence: 70%
“…Subsequently, in a study of men in Wales (N = 173), a handedness and hair whorl association was detected with a higher rate of CCW in the NRH group (54% of 48 NRH) than the RH group (13% of 125 RH) (Beaton & Mellor, 2007). However, a substantially larger study, in a predominantly (90%) male German military sample (N = 1,212), found no significant association between handedness and hair whorl (Jansen et al, 2007).…”
Section: Handedness and Hair Whorlmentioning
confidence: 94%
“…A recent paper seem to confirm Klar's findings: Beaton and Mellor (2007) claim to confirm the association between direction of hair whorl and handedness. Using either 274 or 273 participants (the exact number is not HANDEDNESS AND SCALP HAIR WHORL clear since their narrative indicates 49 ''non-right-handers'' whereas their table lists 48), Beaton and Mellor calculate a significant chi-square.…”
Section: Past Researchsupporting
confidence: 68%
“…Secondly, that the hair whorls were both clockwise is important, given Klar's (2003) claim of a culture-independent relationship between hair whorl, handedness and language lateralization (cf. Weber et al 2006;Beaton & Mellor, 2007;Jansen et al 2007). Unfortunately, it is not clear how this measure interacts with the mechanisms responsible for twinning in monozygotic handedness discordant twins (cf.…”
Section: Between-task Comparisons Brain and Behaviourmentioning
confidence: 99%